Fracking en El Tiempo : ¿contribución a la deliberación democrática? = Fracking in El Tiempo: a contribution to democratic deliberation? (2018)
This article deals with the role of the media in its contribution to citizen deliberation. It investigates whether the way in which El Tiempo covered the fracking issue favored public reasoning by offering quality information. To determine this, 51 journalistic contents were analyzed to establish if the media developed the most outstanding and polemic elements about this technique, namely: its economic, environmental and social incidence. In this regard, a relevant finding is the privilege given to certain sources that showed this extraction technique as an economic necessity and opportunity; a fact that generated a significant bias, since the arguments necessary for a reflective debate, such as the environmental and social risks inherent to fracking, were deliberately overshadowed